The role of buoyancy in the dispersal of marine plastic debris and the impact of biofouling : does size matter? - Fazey, Francesca Margaret Catherine (Percy FitzPatrick Institute of African Ornithology, 2015)
Recent studies suggest that a significant proportion of the plastic pollution that enters the sea is disappearing from the surface, despite being less dense than seawater. Observations across size classes show that it is particularly smaller plastics, <5 mm in length, that are susceptible to removal. The dynamics and transport mechanisms that determine the pathways taken by floating marine plastic debris are poorly understood and the processes causing this disappearance of plastic are unknown. A spatial gradient in the size composition of floating litter has also recently been observed by visual at-sea surveys in the South Atlantic Ocean, where smaller plastic litter items are found in greater relative abundance closer to the coast becoming less frequent with increasing distance out to sea. Conversely, larger, more buoyant plastic items were found to be proportionally more abundant at greater distances away from the coastal source. Both the observations of missing microplastic and the apparent spatial gradient evident in the size composition of dispersing litter suggest that size selective mechanisms are removing smaller fragments of plastics from the surface. The nature of these and the whereabouts and ultimate fate of these smaller plastic fragments is unknown. Two studies were conducted. The first was an empirical investigation to confirm how the size and buoyancy of litter items are influenced by dispersal distances from a point source. Beach littler samples were collected from beaches at increasing distances from a major pollution source: Cape Town in the Western Cape province of South Africa. The size and buoyancy compositions of litter at each distance interval were compared. Mean size and buoyancy increased significantly with increased distance from Cape Town. Mean item volume rose from 5.1 ml to 604 ml. Over 90% of the items recovered closer to Cape Town were in the two lowest buoyancy categories, in contrast to the furthest sampling site, where only 20% of the litter recovered occupied these categories and 55% occupied higher bin ranges. The findings from the beach litter samples were comparable to those of the recent at-sea surveys in the same region and confirmed the spatial gradient in size composition shown by that study. The second study was an experimental investigation into marine biofouling as a possible explanation for the size-selective sinking of smaller plastics at sea. . The study was conducted in situ at the False Bay Yacht Club in Simon's Town in the Western Cape. Samples of highdensity and low-density polyethylene plastic of varying thickness were cut into squares of three different sizes, tethered to exposure rails and submerged approximately 10 cm below the surface for a 12-week study period. A subset was removed bi-weekly, their buoyancy observed and change in dry weight measured. My results showed that both fragment size and material thickness were significant determinants of fouling mass accumulated. Exposure times required for sinking varied from 17 days for the smallest thinnest samples to 66 days for the largest, thickest ones. All sample sizes sank within the study period. Sample volume was a close correlate of time to sinking. Refined versions of these estimates could be scaled by factors such as environmental conditions and proximity to litter inputs, and potentially included into numerical models of floating litter abundance and distribution. Both studies showed that high volume debris items persist longer at the ocean surface.